Water Pollution Index Approaches in Spatial Planning in City Tourism Area (Case Study: Malang Area) - Riyadi, Arief; Rachmansyah, Arief; Yanuwiadi, Bagyo (Journal of Indonesian Tourism and Development Studies, 2018)
As a famous tourism destination in Indonesia, Malang Raya has many interesting places for visiting, like river. River becomes an important part in tourism spatial planning of a region, because almost all the waste from human activities dumped into the river, thus it will affect the quality of the river water. Malang Raya passed by 12 sub-watersheds whereas 4 of them passed 3 districts/cities, namely Metro, Bango, Amprong and Manten sub-watershed. Therefore, it needs an integrated spatial planning between the three regions, especially to support tourism destination. The purpose of this research is to formulate water carrying capacity assessment and its recommendation in spatial planning in Malang area. This is a quantitative-descriptive study using regular monitoring of water quality in 20 rivers surrounding Malang Raya by Malang Department of Environment. The results of this study show that the sub-watershed area of Metro, Bango, Amprong and Manten are classified into mild contaminated. This condition, one of them, is caused by land use changing in upstream areas. A bit more pollution in the river will affect the number of tourist visits to Malang Raya area.Keywords: Amprong, Bango, Manten, Metro, sub-watershed, water pollution index.